Breast conservation surgery (BCS) for breast cancer in a resource limited country- Are we upto the challenge! - Javed, Nida; Rehman, Bushra; Iqbal, Ejaz; Afzal, Sidra; Jamal, Aun; Parvaiz, Muhammad Asad (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse outcomes of breast conservation surgery and to identify the factors that could have affected the outcomes. Method: The retrospectively study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data of breast conservation surgery cases done between January 2011 and October 2014 in order to cover up for the 5-year follow-up of the last enrolled patient. Data, obtained through the institutional information and database system, included disease-recurrence, 5-year disease-free survival and overall survival. Data was statistically analysed using SPSS 20. Results: Of the 553 cases, 417(75%) had no loco-regional recurrence or distant metastasis, while 136(25%) had some form of loco-regional, distant or contralateral metastasis at 5-year follow-up. In patients who had recurrence or metastasis, only progesterone receptor status, nodal status and mode of treatment showed significant association (p<0.05). Mortality at 5-year follow-up was 77(14%). Amongst the patients who died, only progesterone receptor status and nodal status had significant association (p<0.05). Five-year overall survival for the cohort was 476(86%), whereas 5-year disease-free survival was 409(74%). Conclusion: Breast conservation surgery was found to have favourable outcomes, while progesterone status, nodal involvement and mode of treatment significantly affected the outcome. Key Words: Breast cancer, Breast conserving surgery, 5-year disease free survival, 5-year overall survival Continuous...